A Study of Factors for Selection of Building Renovation Contractors Using Analysis Hierarchical Process - Ussavadilokrit, Mongkol; Vatcharotai , Rapeerat (Srinakharinwirot University Engineering Journal, 2022)
Buildings that have been built and that have been used are often damaged over time in both the building and decoration materials. In addition, the utilization of the building space may change according to the purpose of use during each period. Real estate owners therefore need to renovate the building space to make the usable space more suitable. However, renovation projects always encounter various problems and limitations. Therefore, the selection of building renovating contractors with good potential is an important part of helping the work to be successful. The objective of this research was to study the factors for selecting building improvement contractors by using the hierarchical analysis process. The research collected data from related theories and research, including interviews and questionnaires from ten small and medium-sized enterprise project owners involved in the selection of building renovation contractors. The results showed that the main factors in selecting contractors for renovation works were divided into 4 aspects: 1) quality, 2) reliability, 3) price and finance, and 4) working time. The most important minor factors are 1) reasonable time to complete as scheduled, 2) good standards and quality of work, 3) lower prices than competitors, and 4) honesty, respectively. Finally, real estate developers can use the weight of the main and minor factors as a guideline for considering the selection of contractors for renovation works in small and medium-sized enterprise projects.